Polishing material slurry and polishing method for the same
The abrasive slurry with manganese oxide abrasive grains, permanganate ions, and phosphoric acids addresses the issues of poor dispersibility and clogging in existing slurries, achieving enhanced polishing efficiency and easier cleaning.
Patent Information
- Application Number
- JP2024228463
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-16
AI Technical Summary
Existing abrasive slurries containing manganese oxide particles for polishing SiC substrates suffer from poor dispersibility and clogging issues, leading to reduced polishing efficiency and increased cleaning time.
The development of an abrasive slurry comprising manganese oxide abrasive grains with permanganate ions and phosphoric acids, which enhances dispersibility and polishing rate.
The new abrasive slurry exhibits excellent dispersion properties and significantly increases the polishing rate, while also simplifying the cleaning process and reducing environmental impact.
Smart Images

Figure 2025063882000002 
Figure 2025063882000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an abrasive slurry and a polishing method using the same. [Background technology]
[0002] Among semiconductor devices, power semiconductor elements known as power devices are being required to withstand higher voltages and currents by using silicon carbide (SiC), gallium nitride, diamond, etc. instead of the silicon that has traditionally been used as a substrate. Substrates made of these materials have a larger band gap than conventional silicon substrates, making them capable of withstanding higher voltages.
[0003] Among them, a substrate made of silicon carbide (hereinafter referred to as a SiC substrate) is excellent not only in hardness, heat resistance, and chemical stability, but also in terms of cost. On the other hand, since a SiC substrate is harder than a conventional silicon substrate, an abrasive slurry containing manganese oxide particles as abrasive grains has been developed as disclosed in Patent Document 1, for example, as an abrasive slurry used in a polishing step by a so-called CMP (Chemical Mechanical Polishing) method or the like, which is a step of mirror-finishing the surface of a SiC substrate during the manufacturing process of the SiC substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-071787 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, many of the abrasive slurries containing manganese oxide particles as abrasive grains as disclosed in Patent Document 1 have insufficient dispersibility, and since the abrasive slurry is in a viscous liquid state, there is a problem that the supply tube for supplying the abrasive slurry is easily clogged. Furthermore, during the polishing process, the abrasive slurry adheres to the surface of the SiC substrate, which is the object to be polished, and to the polishing pad and other equipment used for polishing, so that when cleaning the polishing pad and SiC substrate after the polishing process, the abrasive slurry is difficult to remove, and the cleaning process takes a long time.
[0006] In view of the above problems, the present invention provides an abrasive slurry having excellent dispersibility and exhibiting a high polishing rate, and a polishing method. [Means for solving the problem]
[0007] The abrasive slurry of the present invention, which has been made to solve the above problems, is characterized by comprising manganese oxide abrasive grains containing manganese oxide particles, permanganate ions, and phosphoric acids. The abrasive slurry of the present invention contains manganese oxide abrasive grains containing manganese oxide particles, permanganate ions, and phosphoric acids, and therefore has excellent dispersibility and exhibits a high removal rate.
[0008] Examples of manganese oxide particles contained in the manganese oxide abrasive grains include manganese oxide (II) (MnO), dimanganese trioxide (III) (Mn2O3), manganese dioxide (IV) (MnO2), trimanganese tetroxide (II, III) (Mn3O4), etc. The manganese oxide abrasive grains may be a mixture of one type or two or more types of manganese oxide particles.
[0009] In addition, the manganese oxide abrasive grains may contain abrasive grains other than the above-mentioned manganese oxide grains, so long as the effect of preventing warpage and cracking due to the Twyman effect on the polished object, for example, a SiC substrate, of the abrasive slurry of the present invention is not impaired. Examples of abrasive grains other than manganese oxide grains include compounds such as oxides, hydroxides, and carbides of at least one element selected from Mg, B, Si, Ce, Al, Zr, Fe, Ti, and Cr, and other carbon materials. Specific examples include alumina, silica, cerium oxide, zirconium oxide, titanium oxide, chromium oxide, iron oxide, magnesium hydroxide, cerium hydroxide, silicon carbide, boron carbide, and diamond. These may be used alone or in combination of two or more. In addition, the manganese oxide grains may be composited with abrasive grains other than manganese oxide grains, for example, manganese oxide grains surface-coated with abrasive grains other than manganese oxide grains, or manganese oxide grains surface-coated with abrasive grains other than manganese oxide grains.
[0010] Moreover, it is preferable that the manganese oxide abrasive grains have a particle size (D50) at 50% of the cumulative volume as measured by a laser diffraction / scattering particle size distribution measurement method of 0.1 μm or more in terms of having a high polishing power, and it is preferable that the particle size is 5.0 μm or less in terms of suppressing roughness of the surface of the workpiece to be polished, such as a SiC substrate. Therefore, it is more preferable that the manganese oxide abrasive grains have a particle size (D50) at 50% of the cumulative volume as measured by a laser diffraction / scattering particle size distribution measurement method of 0.15 μm or more and 4.5 μm or less, and even more preferable that the particle size is 0.2 μm or more and 4.0 μm or less.
[0011] Here, the particle size at 50% cumulative volume (D50) of manganese oxide abrasive grains measured by a laser diffraction / scattering type particle size distribution measurement method is prepared by diluting a mixture of manganese oxide abrasive grains pulverized with beads in the manufacturing method of an abrasive slurry of the present invention described later with water so that the concentration of this mixture becomes about 0.01%. Then, the measurement is performed using a laser diffraction / scattering type particle size distribution measurement device (MT3300EXII manufactured by Microtrackbell Co., Ltd.).
[0012] Furthermore, the content of the manganese oxide abrasive grains contained in the abrasive slurry of the present invention is preferably 0.5% by mass or more and 20% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less, based on the total amount of the abrasive slurry, from the viewpoint of sufficiently increasing the polishing rate of high-hardness materials such as silicon carbide, from the viewpoint of ensuring suitable fluidity of the abrasive grains in the abrasive slurry, and from the viewpoint of preventing aggregation. Moreover, the content of the manganese oxide particles contained in the manganese oxide abrasive grains is more preferably 1% by mass or more and 5% by mass or less, from the viewpoint of sufficiently increasing the polishing rate. In this specification, the content in the abrasive slurry of the present invention is the content in the abrasive slurry before polishing begins, unless otherwise specified.
[0013] Furthermore, the abrasive slurry of the present invention contains, in addition to the manganese oxide abrasive grains described above, permanganate ions (MnO4 - ) The permanganate ion, when used in combination with manganese oxide abrasive grains as an oxidizing agent, can have a high polishing power for high-hardness materials such as silicon carbide. Here, the source of the permanganate ion is preferably a permanganate. Examples of the permanganate include an alkali metal salt of permanganate and an alkaline earth metal salt of permanganate. Furthermore, from the viewpoint of easy availability and improving the polishing efficiency of the abrasive slurry of the present invention, among the permanganates that are the source of the permanganate ion, an alkali metal salt of permanganate is preferred, and sodium permanganate or potassium permanganate is more preferred. Note that these permanganates may be used alone or in combination of two or more.
[0014] In addition, the content of permanganate ions in the polishing slurry of the present invention is preferably 0.5% by mass or more based on the total amount of the polishing slurry of the present invention from the viewpoint of sufficiently increasing the polishing rate.In addition, the content of permanganate ions in the polishing slurry of the present invention is preferably 3.2% by mass or less based on the total amount of the polishing slurry of the present invention from the viewpoint of preventing crystal precipitation due to an increase in the amount of addition, from the viewpoint of ensuring the safety of handling the polishing slurry, and from the viewpoint that the polishing rate tends to saturate even if the amount of addition is increased.That is, the content of permanganate ions is preferably 0.5% by mass or more and 3.2% by mass or less based on the total amount of the polishing slurry of the present invention, and more preferably 1.0% by mass or more and 2.1% by mass or less based on the total amount of the polishing slurry of the present invention.The content of permanganate ions is measured by ion chromatography or absorptiometry.
[0015] Furthermore, the abrasive slurry of the present invention contains phosphoric acid in addition to the manganese oxide abrasive grains and permanganate ions described above. The phosphoric acid can be used in combination with the manganese oxide abrasive grains and permanganate ions to improve the dispersibility of the abrasive slurry of the present invention.
[0016] The phosphoric acid contained in the abrasive slurry of the present invention is preferably, for example, an inorganic phosphorus compound. Specifically, the phosphoric acid compound may be sodium phosphate (trisodium phosphate (anhydrous) (Na3PO4), CAS number: 7601-54-9; trisodium phosphate·12-hydrate (Na3PO4·12H2O), CAS number: 10101-89-0; sodium phosphate monobasic (NaH2PO4), CAS number: 7558-80-7; sodium phosphate dibasic (Na2HPO4), CAS number: 7558-79-4), potassium phosphate (phosphorus Potassium phosphate tripartite (anhydrous) (K3PO4), CAS number: 7778-53-2; potassium phosphate tripartite monohydrate (K3PO4·H2O), CAS number: 27176-10-9; potassium phosphate dibasic trihydrate (K2HPO4·H2O), CAS number: 16788-57-1; potassium phosphate monobasic (KH2PO4), CAS number: 7778-77-0; dibasic potassium phosphate (K2HPO4), CAS number: 7758-11-4.
[0017] As a metaphosphate compound, sodium metaphosphate (NaPO3) n , CAS number: 35270-09-8, potassium metaphosphate (KPO3) n , CAS number: 7790-53-6.
[0018] The hexametaphosphate compound is sodium hexametaphosphate (NaHPO 18 ), CAS number: 10124-56-8.
[0019] Pyrophosphate compounds include sodium pyrophosphate (Sodium pyrophosphate anhydrous (Na4P2O7), CAS number: 7722-88-5; Sodium pyrophosphate decahydrate (Na4P2O7 10H2O), CAS number: 13472-36-1; Sodium acid pyrophosphate (Na2H2P2O7), CAS number: 7758-16-9, and potassium pyrophosphate (K4P2O7), CAS number: 7320-34-5.
[0020] As a polyphosphate compound, sodium polyphosphate (Na3P3O 10 X2), CAS number: 68915-31-1; Potassium polyphosphate (K3P3O 10 X2), CAS number: 68956-75-2.
[0021] As a tripolyphosphate compound, sodium tripolyphosphate (Na5P3O 10 ), CAS number: 7758-29-4, potassium tripolyphosphate (K5P3O 10 ), CAS number: 13845-36-8.
[0022] Further, salts and hydrates thereof may be mentioned. In the case of these salts, alkali metal salts and alkaline earth metal salts are preferred, and sodium salts and potassium salts are more preferred. In particular, in the abrasive slurry of the present invention, from the viewpoint of effective high dispersibility in a small amount and the viewpoint of sufficiently increasing the polishing rate, metaphosphate compounds, hexametaphosphate compounds, pyrophosphate compounds (sodium pyrophosphate and potassium pyrophosphate), polyphosphate compounds (sodium polyphosphate and potassium polyphosphate) and tripolyphosphate compounds are more preferred. These phosphoric acids may be used alone or in combination of two or more.
[0023] Furthermore, among the inorganic phosphorus compounds described above, pyrophosphate compounds are preferred from the viewpoints of high dispersibility and sufficient increase in polishing rate. Among the pyrophosphate compounds, alkali metal salts of pyrophosphate and alkaline earth metal salts of pyrophosphate are more preferred, and sodium pyrophosphate and potassium pyrophosphate are particularly preferred.
[0024] In addition, the content of phosphoric acid in the abrasive slurry of the present invention is preferably 0.01% by mass or more based on the total amount of the abrasive slurry of the present invention from the viewpoint of dispersibility.In addition, the content of phosphoric acid in the abrasive slurry of the present invention is preferably 0.1% by mass or less based on the total amount of the abrasive slurry of the present invention, because the polishing rate tends to saturate even if the amount of phosphoric acid is increased.That is, the content of phosphoric acid is preferably 0.01% by mass or more to 0.1% by mass or less based on the total amount of the abrasive slurry of the present invention, and more preferably 0.02% by mass or more based on the viewpoint of improving dispersibility, and more preferably 0.05% by mass or less based on the viewpoint of sufficiently increasing the polishing rate.In addition, the content of phosphoric acid in this specification is the total amount of phosphoric acid classified as phosphoric acid, unless otherwise specified.
[0025] Furthermore, the content of the phosphoric acid in the abrasive slurry of the present invention, expressed as a mass ratio to the content of the manganese oxide abrasive grains in the abrasive slurry of the present invention, is preferably 0.5% to 5.0%, more preferably 0.8% to 3.0%, and even more preferably 1.0% to 2.0%.
[0026] The abrasive slurry of the present invention is characterized in that it further contains a cellulose-based surfactant and / or a cationic surfactant. The abrasive slurry of the present invention can have improved low friction properties by further containing a cellulose-based surfactant and / or a cationic surfactant.
[0027] As the cellulose-based surfactant, anionic surfactants, cationic surfactants, and nonionic surfactants are all known. First, anionic surfactants include those in which a negative group, such as a carboxyl group, an alkoxyl group, or a hydroxyl group, is introduced into the cellulose skeleton. In addition, cationic surfactants include cationic cellulose. Furthermore, nonionic surfactants include alkyl celluloses such as ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, and hydroxypropyl methyl cellulose.
[0028] Among these cellulose surfactants, anionic surfactants are preferred, and those containing a carboxyl group are more preferred, and carboxymethylcellulose and its derivatives are preferred from the viewpoint of low friction. Carboxymethylcellulose is a compound in which a carboxymethyl group is bonded to a part of the hydroxyl group of a glucopyranose monomer constituting a cellulose skeleton. In addition, examples of the carboxymethylcellulose derivative include alkali metal salts of carboxymethylcellulose, specifically salts such as sodium or potassium salts. Furthermore, examples of the carboxymethylcellulose derivative include those in which a hydroxyl group, an alkyl group, or the like is bonded to the side chain of carboxymethylcellulose within a range that does not lose the surfactant effect of carboxymethylcellulose. Other examples of the cellulose surfactant include crystalline cellulose and its modified products (for example, Avicel manufactured by Asahi Kasei Corporation). It should be noted that one or more of these cellulose surfactants may be used in combination.
[0029] The cationic surfactant may be an amine salt surfactant or a quaternary ammonium salt surfactant, and is preferably one having a quaternary ammonium ion site. Here, the cationic surfactant having a quaternary ammonium ion site may be, for example, a salt represented by the following general formula (1):
[0030] [ka] (In the above general formula (1), R1, R2, R3, and R4 are each independently an alkyl group, an aryl group, or an arylalkyl group, or R1, R2, and R3 are bonded to form a pyridine ring, and R4 is an alkyl group, an aryl group, or an arylalkyl group; X - is a monovalent anion.)
[0031] In the above general formula (1), the alkyl group represented by R1, R2, R3, and R4 preferably has 1 to 20 carbon atoms, specifically, methyl group, ethyl group, propyl group, isopropyl group, n-butyl group, s-butyl group, t-butyl group, isobutyl group, amyl group, isoamyl group, t-amyl group, hexyl group, heptyl group, isoheptyl group, t-heptyl group, n-octyl group, isooctyl group, 2-ethylhexyl group, t-octyl group, nonyl group, isononyl group, decyl group, isodecyl group, undecyl group, dodecyl group, tridecyl group, isotridecyl group, tetradecyl group, hexadecyl group, octadecyl group, icosyl group, etc., and linear group is preferable. The aryl group represented by R1, R2, R3, and R4 is preferably a phenyl group. The arylalkyl group represented by R1, R2, R3, and R4 is preferably a benzyl group, a phenethyl group, or the like. - The monovalent anion represented by is preferably a halide ion. The halide ion is preferably a chloride ion or a bromide ion. The aromatic ring in the aryl group or arylalkyl group represented by R1, R2, R3, and R4 and the pyridine ring formed by bonding R1, R2, and R3 may be substituted with an alkyl group or an amino group, and the methylene group in the arylalkyl group may be replaced with -O-. The pyridine ring formed by bonding R1, R2, and R3 may be condensed with a benzene ring.
[0032] The cationic surfactant represented by the above general formula (1) is, for example, distearyldimethylammonium chloride (rational formula C 18 H 37 N + C 18 H 37 (CH3)2 Cl - ), benzalkonium chloride (chemical formula C6H5CH2N + (CH3)2RCl - (R=C8H 17 ~C 18 H 37 , long chain alkyl), benzethonium chloride (molecular formula C 27 H 42 ClNO2), cetylpyridinium chloride (molecular formula C 21 H38 NCl), hexadecyltrimethylammonium bromide (with rational formula (C 16 H 33 )N + (CH3)3Br - ), dequalinium chloride (molecular formula C 30 H 40 C l2 N4) etc.
[0033] In addition, the total content of the cellulose surfactant and / or cationic surfactant in the abrasive slurry of the present invention is preferably 0.1% by mass or more based on the total amount of the abrasive slurry of the present invention from the viewpoint of improving low friction. In addition, the total content of the cellulose surfactant and / or cationic surfactant in the abrasive slurry of the present invention is preferably 1% by mass or less based on the total amount of the abrasive slurry of the present invention from the viewpoint of sufficiently increasing the polishing rate. That is, the total content of the cellulose surfactant and / or cationic surfactant is preferably 0.1% by mass or more to 1% by mass or less based on the total amount of the abrasive slurry of the present invention, and more preferably 0.1% by mass or more to 0.5% by mass or less. In this specification, the total content of the cellulose surfactant and / or cationic surfactant refers to the content of only one of the cellulose surfactant and / or cationic surfactant when only one of them is contained, and refers to the total amount of them when both are contained, unless otherwise specified.
[0034] The abrasive slurry of the present invention is characterized in that the content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, the content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, and the content of the phosphoric acids is 0.01% by mass or more and 0.1% by mass or less. As described above, the abrasive slurry of the present invention is preferable in that the content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, the content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, and the content of the phosphoric acids is 0.01% by mass or more and 0.1% by mass or less, in that the slurry has excellent dispersibility and exhibits a high polishing rate.
[0035] The abrasive slurry of the present invention is characterized in that the content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, the content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, the content of the phosphoric acids is 0.01% by mass or more and 0.1% by mass or less, and the total content of the cellulose-based surfactant and / or the cationic surfactant is 1.0% by mass or less. As described above, the abrasive slurry of the present invention is preferable from the viewpoints of excellent dispersibility, high polishing rate, and low friction, when the content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, the content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, the content of the phosphoric acids is 0.01% by mass or more and 0.1% by mass or less, and the total content of the cellulose-based surfactant and / or the cationic surfactant is 1.0% by mass or less.
[0036] Here, the abrasive slurry of the present invention contains a dispersion medium for dissolving or dispersing the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acids, and cellulose-based surfactants and / or cationic surfactants. The dispersion medium is preferably water, a water-soluble organic solvent such as alcohol or ketone, or a mixture thereof, in order to sufficiently increase the polishing rate, and more preferably water. The content of the dispersion medium is preferably 60% by mass or more and 99.9% by mass or less, and more preferably 80% by mass or more and 90% by mass or less, based on the total amount of the abrasive slurry.
[0037] Furthermore, the abrasive slurry of the present invention may contain any additive other than the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acids, cellulose-based surfactants, and / or cationic surfactants, and the dispersion medium. Here, the optional additives include dispersants, pH adjusters, viscosity adjusters, chelating agents, and rust inhibitors. The content of the optional additives is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, based on the total amount of the abrasive slurry of the present invention.
[0038] The abrasive slurry of the present invention can be in a form in which the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acids, cellulose-based surfactants, and / or cationic surfactants, dispersion medium, and optional additives are appropriately mixed, and may be, for example, a kit in which these components are divided into two or more agents. The kit may be configured in any form that allows the abrasive slurry to fully exert its polishing ability when prepared.
[0039] A polishing method for polishing an object to be polished using the above-mentioned abrasive slurry of the present invention will be described below.
[0040] The polishing method includes supplying the abrasive slurry of the present invention to a polishing pad, contacting the polished surface of the workpiece with the polishing pad, and polishing by the relative movement between the two. Here, the method may be a method of pouring the abrasive slurry of the present invention, or a method of circulating the abrasive slurry of the present invention, in which the abrasive slurry of the present invention that has been supplied to the polishing pad and used for polishing is recovered, and the recovered abrasive slurry of the present invention is supplied to the polishing pad again by repeatedly performing the operation. Since the abrasive slurry of the present invention can be circulated and repeatedly used to polish the workpiece, the amount of use can be reduced. Here, the polishing pad can be, for example, a pad made of a nonwoven fabric that has been used conventionally, a pad made by impregnating it with a resin such as polyurethane or epoxy, or a suede material. The polishing pressure is 0.5×10 4 Pa or more 1.0×10 5 Pa or less, especially 1.0×10 4 Pa or more 5.0×10 4 It is preferable that the pressure is not more than Pa in terms of the polishing force and ease of handling of the polishing jig, etc. The supply rate of the abrasive slurry is preferably 10 mL / min to 500 mL / min, and more preferably 50 mL / min to 250 mL / min.
[0041] The object to be polished by the abrasive slurry of the present invention is a high-hardness material having a Mohs hardness of 8 or more. Here, the Mohs hardness is a numerical value of hardness based on the scratching of a standard material, and can be measured by a conventional method using a Mohs hardness meter. Standard materials are designated from 1 to 10 in order of Mohs hardness from softest to softest, and specific standard materials are talc with a Mohs hardness of 1, gypsum with a Mohs hardness of 2, calcite with a Mohs hardness of 3, fluorite with a Mohs hardness of 4, apatite with a Mohs hardness of 5, orthoclase with a Mohs hardness of 6, quartz with a Mohs hardness of 7, topaz with a Mohs hardness of 8 or more, for example, silicon carbide (Mohs hardness of about 9), gallium nitride (Mohs hardness of about 9), diamond, etc.
[0042] The abrasive slurry of the present invention can be used in a finishing CMP (Chemical Mechanical Polishing) process after lapping of a substrate made of a high hardness material. In particular, the abrasive slurry of the present invention can be used to polish a substrate made of silicon carbide (SiC), i.e., a SiC substrate, and can sufficiently increase the polishing rate and effectively prevent warping and cracking caused by the Twyman effect. A single crystal silicon carbide substrate is usually used as the SiC substrate, and the crystal system thereof is usually hexagonal or rhombohedral, and the hexagonal crystal is preferable from the viewpoint of exerting the effect of the abrasive slurry that can prevent warping and cracking caused by the Twyman effect. The polymorphism of the hexagonal crystal is 2H, 4H, 6H, 8H, and 10H. The polymorphism of the rhombohedral crystal is 15R.
[0043] Next, a method for producing the above-mentioned abrasive slurry of the present invention will be described below.
[0044] First, pure water, manganese dioxide (abrasive grains, MnO2), phosphoric acid (e.g., sodium pyrophosphate), and beads (zirconia, φ0.4 mm) are placed in a container, the container is set on a paint shaker (60 Hz), and the container is rotated at high speed to mix and grind the manganese dioxide (abrasive grains, MnO2).
[0045] The mixture containing the mixed and ground manganese dioxide (abrasive grains, MnO2) in the container is separated from the beads using a centrifuge (Hitachi Koki himac CT 6E) or the like, and the supernatant liquid is collected.
[0046] The solids concentration in the collected supernatant, i.e., the manganese oxide abrasive grain concentration, is measured using a heating moisture meter, and pure water is added to the supernatant to obtain a predetermined concentration, thereby obtaining an abrasive slurry intermediate. A cellulose-based surfactant and / or a cationic surfactant may be added to the obtained abrasive slurry intermediate.
[0047] The abrasive slurry of the present invention is obtained by mixing the abrasive slurry intermediate with potassium permanganate (KMnO4).
[0048] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention
[0049] The abrasive slurry of the present invention has excellent dispersibility and can sufficiently increase the removal rate. [Brief description of the drawings]
[0050] [Figure 1] 1 is a table showing the physical property values and measurement results of abrasive slurries according to Examples 1 to 10 and Comparative Examples 1 to 5. BEST MODE FOR CARRYING OUT THEINVENTION
[0051] The abrasive slurry according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.
[0052] Example 1 Pure water, manganese dioxide (MnO2) as abrasive grains, sodium pyrophosphate as phosphoric acid (specifically, sodium pyrophosphate decahydrate (Na4P2O7·10H2O), CAS number: 13472-36-1), and beads (zirconia, φ0.4 mm) were placed in a container, and the container was set on a paint shaker (60 Hz) and rotated at high speed to mix and grind the manganese dioxide. The contents of these components were adjusted so that the manganese dioxide content was 30 mass% and the sodium pyrophosphate content was 0.3 mass% relative to the total amount of the abrasive slurry of Example 1.
[0053] The mixture containing the mixed and ground manganese dioxide in the container was separated from the beads using a centrifuge (himac CT 6E manufactured by Hitachi Koki Co., Ltd.) or the like, and the supernatant was collected. The supernatant obtained in this step will be the measurement sample before the addition of potassium permanganate in the dispersibility test described below.
[0054] The solids concentration in the collected supernatant, ie, the manganese oxide abrasive grain concentration, was measured using a heating moisture meter, and pure water was added to adjust the concentration to a predetermined level, thereby obtaining an intermediate abrasive slurry.
[0055] Then, the abrasive slurry intermediate was mixed with an aqueous potassium permanganate (KMnO4) solution having a KMnO4 mass% concentration of 3.2 mass%, to obtain an abrasive slurry according to Example 1. The content of permanganate ions was adjusted to be 1.2 mass% with respect to the total amount of the abrasive slurry according to Example 1. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content according to Example 1 was 1.0%. The abrasive slurry according to Example 1 obtained in this process is the measurement sample after the addition of potassium permanganate in the dispersibility test described later. The composition of the abrasive slurry shown in FIG. 1 is the composition of the final product.
[0056] Example 2 In Example 2, the abrasive slurry of Example 2 was obtained by carrying out the same manufacturing method as in Example 1, except that trisodium phosphate was used instead of sodium pyrophosphate used in Example 1 so as to be 0.3 mass% relative to the total mass of the abrasive slurry of Example 2. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content in Example 2 was 1.0%.
[0057] Example 3 In Example 3, in addition to the components used in Example 1, carboxymethylcellulose was added as a cellulose-based surfactant to the abrasive slurry intermediate of Example 1 so as to be 0.25 mass% relative to the total amount of the abrasive slurry of Example 3, before mixing the abrasive slurry intermediate of Example 1 with potassium permanganate (KMnO4), and the mixture was mixed. The same manufacturing method as in Example 1 was carried out to obtain an abrasive slurry of Example 3. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content in Example 3 was 1.0%.
[0058] Example 4 In Example 4, the abrasive slurry of Example 4 was obtained by carrying out the same manufacturing method as in Example 1, except that the content of manganese dioxide (MnO2) as abrasive grains was adjusted to 0.5 mass% with respect to the total amount of the abrasive slurry of Example 4. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content of Example 4 was 4.0%.
[0059] Example 5 In Example 5, the abrasive slurry of Example 5 was obtained by carrying out the same manufacturing method as in Example 1, except that the content of manganese dioxide (MnO2) as abrasive grains was adjusted to 20 mass% with respect to the total amount of the abrasive slurry of Example 5. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content of Example 5 was 0.1%.
[0060] Example 6 In Example 6, the abrasive slurry of Example 6 was obtained by carrying out the same manufacturing method as in Example 1, except that the abrasive slurry intermediate was mixed with an aqueous potassium permanganate (KMnO4) solution with a KMnO4 mass% concentration of 5.6 mass%, and the content of permanganate ions was adjusted to 3.2 mass% with respect to the total amount of the abrasive slurry of Example 6. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content in Example 6 was 1.0%.
[0061] Example 7 In Example 7, the abrasive slurry of Example 7 was obtained by carrying out the same manufacturing method as in Example 1, except that the content of sodium pyrophosphate was adjusted to 0.01 mass% with respect to the total amount of the abrasive slurry of Example 7. The mass ratio of the total content of phosphoric acids to the content of manganese oxide abrasive grains in Example 7 was 0.5%.
[0062] Example 8 In Example 8, the abrasive slurry of Example 8 was obtained by carrying out the same manufacturing method as in Example 1, except that the content of sodium pyrophosphate was adjusted to 0.1 mass% with respect to the total amount of the abrasive slurry of Example 8. The mass ratio of the total content of phosphoric acids to the content of manganese oxide abrasive grains in Example 8 was 5.0%.
[0063] Example 9 In Example 9, the content of sodium pyrophosphate was adjusted to 0.018 mass% based on the total amount of the abrasive slurry according to Example 9, and other phosphoric acids (specifically, tripotassium phosphate (anhydrous) (K3PO4), CAS number: 7778-53-2, and sodium metaphosphate (NaPO3) n , CAS number: 35270-09-8, potassium pyrophosphate (K4P2O7), CAS number: 7320-34-5, sodium polyphosphate (Na3P3O 10 X2), CAS number: 68915-31-1, and sodium tripolyphosphate (Na5P3O 10A similar manufacturing method to that of Example 1 was carried out, except that the content of phosphoric acid was adjusted to 0.002 mass% (the total content of phosphoric acid was 0.02 mass%), to obtain an abrasive slurry of Example 9. The mass ratio of the total content of phosphoric acid to the manganese oxide abrasive grain content of Example 9 was 1.0%.
[0064] Example 10 In Example 10, the same manufacturing method as in Example 1 was carried out, except that before mixing the abrasive slurry intermediate of Example 1 with potassium permanganate (KMnO4), carboxymethylcellulose was added as a cellulose-based surfactant to the abrasive slurry intermediate of Example 1 so as to be 0.1 mass% relative to the total amount of the abrasive slurry of Example 10, and mixed, to obtain the abrasive slurry of Example 10. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content in Example 10 was 1.0%.
[0065] Comparative Example 1 In Comparative Example 1, the same manufacturing method as in Example 1 was carried out except that no phosphoric acid was added, to obtain an abrasive slurry according to Comparative Example 1. The mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Comparative Example 1 was 0.0%.
[0066] Comparative Example 2 In Comparative Example 2, instead of manganese dioxide (MnO2) used in Example 1, silicon dioxide (SiO2) was used so as to be 2.0 mass% relative to the total amount of the abrasive slurry in Comparative Example 2, and potassium permanganate (KMnO4) was not added to the abrasive slurry intermediate, but the same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry in Comparative Example 2. The mass ratio of the total content of phosphoric acids to the content of silicon oxide abrasive grains in Comparative Example 2 was 1.0%.
[0067] Comparative Example 3 In Comparative Example 3, the abrasive slurry of Comparative Example 3 was obtained by carrying out the same manufacturing method as in Example 1, except that the abrasive slurry intermediate was mixed with an aqueous potassium permanganate (KMnO4) solution with a KMnO4 mass % concentration of 5.6 mass % and the content of permanganate ions was adjusted to 4 mass % with respect to the total amount of the abrasive slurry of Comparative Example 3. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content of Comparative Example 3 was 1.0%.
[0068] Comparative Example 4 In Comparative Example 4, the abrasive slurry of Comparative Example 4 was obtained by carrying out the same manufacturing method as in Example 1, except that the content of sodium pyrophosphate was adjusted to 0.001 mass% with respect to the total amount of the abrasive slurry of Comparative Example 4. The mass ratio of the total content of phosphoric acids to the content of manganese oxide abrasive grains in Comparative Example 4 was 0.05%.
[0069] Comparative Example 5 In Comparative Example 5, the abrasive slurry of Comparative Example 5 was obtained by carrying out the same manufacturing method as in Example 1, except that the content of sodium pyrophosphate was adjusted to 0.5 mass% with respect to the total amount of the abrasive slurry of Comparative Example 5. The mass ratio of the total content of phosphoric acids to the content of manganese oxide abrasive grains in Comparative Example 5 was 25%.
[0070] The following physical properties were measured for the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 to 5. The measured physical properties and the methods for measuring the physical properties are shown below, and the measurement results are shown in FIG.
[0071] <Particle size evaluation> The mixtures containing the abrasive grains mixed and ground in a paint shaker in the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 to 5 were diluted with water to a concentration of about 0.01% to prepare measurement samples. Then, the particle size at a volumetric cumulative fraction of 50% (D50) was measured using a laser diffraction / scattering particle size distribution measuring device (MT3300EXII, manufactured by Microtrackbell Corporation).
[0072] <Dispersibility evaluation> The dispersibility of the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 and 3 to 5 was evaluated before and after the addition of potassium permanganate, which is a source of permanganate ions.
[0073] First, the dispersibility before the addition of potassium permanganate was evaluated as follows. The mixture containing the abrasive grains mixed and ground by a paint shaker in the abrasive slurries according to Examples 1 to 10 and Comparative Examples 1 and 3 to 5 was diluted with water so that the concentration of the mixture was about 0.01 mass %, to prepare a measurement sample. Then, the particle size (D50) at a volume-based cumulative fraction of 50% was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrackbell Corporation: MT3300EXII), and if D50 was 0.6 μm or less, it was evaluated as "◯ (Good)", and if D50 was more than 0.6 μm, it was evaluated as "× (Bad)".
[0074] Next, the dispersibility after the addition of potassium permanganate was evaluated as follows. Measurement samples were prepared by diluting the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 and 3 to 5 with water so that the concentration was about 0.01% by mass. Then, the particle size (D50) at a volume-based cumulative fraction of 50% was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrackbell Co., Ltd.: MT3300EXII), and if D50 was 0.6 μm or less, it was evaluated as "Good", and if D50 was more than 0.6 μm, it was evaluated as "Bad". Note that the abrasive slurry of Comparative Example 2 did not have potassium permanganate (KMnO4) added to its abrasive slurry intermediate, so the above-mentioned dispersibility evaluation was not performed.
[0075] Adhesion Evaluation The adhesion of the abrasive slurries according to Examples 1 to 10 and Comparative Examples 1 to 5 was judged by a tester by visually checking the adhesion state of each abrasive slurry to the container (wide-mouthed bottle made by AS ONE, Eye Boy 250 ml) containing the sample used in the above-mentioned evaluation of dispersibility after the addition of potassium permanganate, when the container was inverted, as follows. When the container containing the sample was inverted, if the sample did not adhere to the container, it was evaluated as "〇〇 (Very Good)", if the sample adhered only to the bottom of the container, it was evaluated as "〇 (Good)", and if the sample adhered to the bottom and side or side of the container, it was evaluated as "× (Bad)". Note that the abrasive slurry according to Comparative Example 2 was a sample in which potassium permanganate (KMnO4) was not added to the abrasive slurry intermediate.
[0076] <Polishing test> The polishing rates of the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 to 5 were evaluated by the following procedure. The object to be polished was a CMP-processed 4H-SiC substrate with a diameter of 4 inches and an off angle of 4°. The polishing test was performed on the Si surface of the substrate. The polishing device used was a single-sided polisher BC-15 manufactured by MAT Corporation. The polishing pad attached to the platen was an IC1000 manufactured by Nitta DuPont. The platen rotation speed was set to 60 rpm, and the outer peripheral speed was set to 7,136 cm / min. The carrier rotation speed was set to 60 rpm, and the outer peripheral speed was set to 961 cm / min. Furthermore, the load during polishing was 2.8 psi (approximately 1.96×10 4 The polishing rate was calculated from the difference in the mass of the substrate before and after polishing, after polishing for 1 hour, as shown in Table 1. If the polishing rate was 0.10 μm / h or more, it was evaluated as "Good", and if the polishing rate was less than 0.10 μm / h, it was evaluated as "Bad".
[0077] <Crystallization test> Each sample of abrasive slurry according to Examples 1 to 10 and Comparative Examples 1 to 5 was prepared. Each prepared sample was stored in a refrigerator set at 10° C. for 24 hours. Then, each sample was taken out of the refrigerator, and the solid content concentration in each sample, i.e., the total value of the manganese oxide abrasive grain concentration and the potassium permanganate concentration, was determined using a heating moisture meter. If the solid content concentration after storage maintained 90% or more of the solid content concentration before storage, it was evaluated as "Good (◯)", and if the solid content concentration after storage maintained less than 90% of the solid content concentration before storage, it was evaluated as "Bad (×)".
[0078] <Friction characteristic evaluation> The friction characteristics of the abrasive slurries according to Examples 1, 3, and 10 were evaluated as follows. A polishing pad (IC1000 manufactured by Nitta DuPont) was attached and fixed on the platen of a polishing machine, and 1 L of the abrasive slurries according to Examples 1, 3, and 10 was supplied at a supply rate of 200 mL / min onto the polishing pad in a circulating manner. A workpiece was placed on the polishing pad as an object to be polished. Furthermore, while a spring balance was hung on the workpiece, the platen of the polishing machine was rotated, and the workpiece was rotated in the same direction as the platen by the forced drive unit. Here, the forced drive unit is provided with a rotating roller that can contact the workpiece, and the rotating roller is rotated to rotate the workpiece. Then, the spring balance was pulled in the direction in which the workpiece was separated from the forced drive unit, and the rotation of the workpiece was stopped by the forced drive unit separating the rotating roller from the workpiece. The digital display value (i.e., pulling force) displayed on the spring balance 30 seconds after the rotation of the workpiece stopped was measured. The tensile force thus measured was divided by the load of the workpiece to determine the friction coefficient of the abrasive slurries of Examples 1, 3, and 10. If the friction coefficient was 0.35 or less, it was evaluated as "〇〇 (Very Good)", if the friction coefficient was more than 0.35 and less than 0.38, it was evaluated as "〇 (Good)", and if the friction coefficient was more than 0.38, it was evaluated as "× (Bad)".
[0079] As shown in FIG. 1, the abrasive slurries of Examples 1 to 10 had excellent dispersibility, since the particle size at 50% cumulative volume fraction (D50) in the particle size distribution, measured by laser diffraction / scattering method, was 0.6 μm or less both before and after the addition of potassium permanganate, which is a source of permanganate ions.
[0080] In the case of the abrasive slurries of Examples 1, 3 to 6, and 8 to 10, when the container containing the sample was inverted, the adhesion state of the abrasive slurries to the container was checked, and the sample did not adhere to the container, and the adhesion was very good. In addition, in the case of the abrasive slurries of Examples 2 and 7, the sample adhered only to the bottom of the container, and the adhesion was good.
[0081] The abrasive slurries according to Examples 1 to 10 exhibited high polishing rates, since they had polishing rates of 0.10 μm / h or more.
[0082] The abrasive slurries of Examples 1 to 10 were stored in a refrigerator set at 10°C for 24 hours, and the solid content after storage maintained 90% or more of the solid content before storage, indicating that no crystals were precipitated.
[0083] The abrasive slurries of Examples 1, 3, and 10 had a friction coefficient of 0.38 or less, and thus realized low friction properties.
[0084] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]
[0085] The abrasive slurry according to the present invention has excellent dispersibility and high polishing rate, and is suitable as an abrasive for polishing objects made of high hardness materials.In addition, the abrasive slurry according to the present invention has excellent dispersibility, and therefore it is easy to clean the objects to be polished, such as SiC substrates and polishing pads, and can reduce the amount of cleaning water used, can shorten the cleaning time, and can reduce the amount of wastewater to be treated, which leads to a reduction in environmental load.In addition, the abrasive slurry according to the present invention has a high polishing rate, and therefore can shorten the polishing process time.
Claims
1. manganese oxide abrasive grains containing manganese oxide particles; Permanganate ions, Phosphates, 13. An abrasive slurry comprising:
2. 2. The abrasive slurry according to claim 1, wherein the phosphoric acid is an inorganic phosphorus compound.
3. 3. The abrasive slurry according to claim 2, wherein the inorganic phosphorus compound is a pyrophosphate compound.
4. 2. The abrasive slurry according to claim 1, further comprising a cellulose-based surfactant and / or a cationic surfactant.
5. 5. The abrasive slurry according to claim 4, wherein the cellulose-based surfactant contains carboxymethyl cellulose.
6. The content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, The content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, 4. The abrasive slurry according to claim 1, wherein the content of the phosphoric acid is 0.01% by mass or more and 0.1% by mass or less.
7. The content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, The content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, The content of the phosphoric acid is 0.01% by mass or more and 0.1% by mass or less, 6. The abrasive slurry according to claim 4, wherein the total content of the cellulose-based surfactant and / or the cationic surfactant is 1.0 mass % or less.
8. A polishing method comprising polishing an object to be polished with the abrasive slurry according to any one of claims 1 to 5.
9. A polishing method comprising polishing an object to be polished with the abrasive slurry according to claim 6.
10. A polishing method comprising polishing an object to be polished with the abrasive slurry according to claim 7.
Citation Information
Patent Citations
Polishing material slurry and polishing method
JP2017071787A